Predicting response to vascular endothelial growth factor inhibitor and chemotherapy in metastatic colorectal cancer. - O'SULLIVAN, JACINTHA (My University, 2014)
Background Bevacizumab improves progression free survival (PFS) and overall survival (OS) in metastatic colorectal cancer patients however currently there are no biomarkers that predict response to this treatment. The aim of this study was to assess if differential protein expression can differentiate patients who respond to chemotherapy and bevacizumab, and to assess if select proteins correlate with patient survival. Methods Pre-treatment serum from patients with metastatic colorectal cancer (mCRC) treated with chemotherapy and bevacizumab were divided into responders and nonresponders based on their progression free survival (PFS). Serum samples underwent immunoaffinity depletion and protein expression was analysed using two-dimensional difference gel electrophoresis (2D-DIGE), followed by LC-MS/MS for protein identification. Validation on selected proteins was performed on serum and tissue samples from a larger cohort of patients using ELISA and immunohistochemistry, respectively (n = 68 and n = 95, respectively). Results 68 proteins were identified following LC-MS/MS analysis to be differentially expressed between the groups. Three proteins (apolipoprotein E (APOE), angiotensinogen (AGT) and vitamin D binding protein (DBP)) were selected for validation studies. Increasing APOE expression in the stroma was associated with shorter progression free survival (PFS) (p = 0.0001) and overall survival (OS) (p = 0.01), DBP expression (stroma) was associated with shorter OS (p = 0.037). Increasing APOE expression in the epithelium was associated with a longer PFS and OS, and AGT epithelial expression was associated with a longer PFS (all p < .05). Increasing serum AGT concentration was associated with shorter OS (p = 0.009). Conclusions APOE, DBP and AGT identified were associated with survival outcomes in mCRC patients treated with chemotherapy and bevacizumab.
PUBLISHED
Keywords: Colorectal cancer; Bevacizumab; 2D-DIGE; Biomarker; Proteomics; Colorectal cancer; Bevacizumab; 2D-DIGE; Biomarker; Proteomics; Cancer; Biomedical sciences